Learning Readiness Profile of 10th Grade SMK Students in Civic Education with Social-Emotional Worksheets - Thoriq Abdul Aziz; Arini Fathia Handayani (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
This study aims to analyze the learning readiness profile of 10th-grade students at SMK Negeri 5 Garut in Civic Education (Civic Education) lessons facilitated by social-emotional worksheets (LKPD) A quantitative descriptive method was employed, involving the distribution of social-emotional student worksheet and a Google Form questionnaire to 36 students. The results reveal that 73.8% of students exhibit a medium to high level of learning readiness in Civic Education. These findings indicate that the integration of Social Emotional Learning (SEL) approaches within student worksheet contributes positively to the enhancement of students' affective aspects and civic dispositions, which are essential goals of Civic Education. Furthermore, these results suggest the potential of SEL-based student worksheet in facilitating character development aligned with the Profil Pelajar Pancasila, particularly in the dimensions of independence, critical thinking, and collaboration.